A Retrospective Clinicoradiologic Study of 126 Cerebellopontine Angle Tumors to Predict the Outcome of House–Brackmann Status to Prognosticate Them: A Single-Center Tertiary Care Perspective - Sambuddha Dhar; Anurag Sahu; Barnava Pal; Kulwant Singh (Indian Journal of Neurosurgery)
Introduction House–Brackmann (HB) grading had been described to quantify the facial nerve involvement in cerebellopontine angle (CPA) tumors, a very common tumor in neurosurgical practice. Very few studies have specifically looked into the factors predicting the facial nerve morbidity and its severity. Here, we try finding these while going through the clinicoradiologic factors and its natural course to help us prognosticate the patients. Objective To analyze the size of tumor and duration of symptoms to predict the severity of HB status of facial nerve presentation and outcome, and to study the course of the disease to help prognosticate the patients with respect to facial nerve status. Materials and Methods This was a retrospective analysis of 126 operated CPA tumors, where we studied the natural course of HB status with respect to size and duration of symptoms of patients at our institute between December 2016 to February 2020. Results Average duration of symptoms were 33.8 days with increasing risk of HB outcome after 36 days of symptoms. All patients improved to their preoperative facial nerve status at 3 months and only 18 maintained the worsened HB status. Average size of tumor was 3.53 cm, and size higher than 3.8 cm was associated with poorer HB outcome. Conclusion Although there can be a significant deterioration of HB status in immediate postoperative period, it improves to preoperative status in due time. Tumor larger than 3.8 cm and symptom duration more than 36 days are two important factors predicting poorer HB outcome.